Knowledge, attitude and practices about cervical cancer screening among nursing staff in rural tertiary care center - Vishwakarma, Soniya; Rawat, Rajani; Mittal, Nupur; Shree, Pragya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cervical cancer is the second most common cancer among women worldwide. The knowledge and attitude of nursing personnel towards cervical cancer screening can grossly influence the community. As the doctor to patient ratio is low in India, staff nurses if trained can act both as health educators and service providers. Objectives of the study were to determine the baseline information about the knowledge of cervical cancer and explore attitude and practice of Pap smear screening among staff nurses. Methods: In this cross-sectional study sample of 100 nurses was selected randomly out of the total 445 nurses employed in the hospital at a rural tertiary care centre from August 2016 to October 2016. A self-administered, structured, open ended and pretested questionnaire comprising of questions on the general characteristics, awareness, perceptions and actual practices of nursing personnel was used to gather information about cervical screening. Results: In this study, 82% knew that Pap smear can detect cancer. About 48% knew that it can present as post-menopausal bleeding and 32% of the respondents knew that HPV is a risk factor for cancer cervix, but only 30% knew about HPV vaccine and only 35% have ever been screened. Conclusions: The study showed that, knowledge about cancer cervix, screening and practice of Pap smear is low among nursing staff. There is an urgent need for integration of cervical cancer prevention issues in the nurses existing training curriculum.